Refresh your livestock knowhow - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
New and updated courses and workshops, In English, for mid-career professionals in livestock management and policy setting are on offer at the International Agricultural Centre (IAC) in The Netherlands: Pig production, the environment and the...